2022
DOI: 10.21037/atm-22-3593
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of new therapeutic targets for viral hepatic fibrosis, alcoholic hepatic fibrosis, and non-alcoholic hepatic fibrosis

Abstract: Background: Hepatic fibrosis is a widespread disease worldwide. Millions of people lose their lives due to hepatic fibrosis every year. The main causes of hepatic fibrosis include viral infection, alcoholism, and obesity. Many studies have been conducted on the single factors that cause hepatic fibrosis; however, no studies have examined whether hepatic fibrosis caused by multiple factors has concomitant expression molecules and signaling pathways. In this study, we sought to analyze the common differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that defective insulin secretion in cystic fibrosis affects growth before hyperglycemia occurs, which is also confirmed by another study [ 42 , 43 ]. Many researchers found that bile secretion was related to fibrosis disease [ 44 ]. Zhang et al found that B7-33 which targets relaxin family peptide receptors can activate hepatic stellate cells (HSCs) can weaken the fibrogenic properties of activated HSCs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that defective insulin secretion in cystic fibrosis affects growth before hyperglycemia occurs, which is also confirmed by another study [ 42 , 43 ]. Many researchers found that bile secretion was related to fibrosis disease [ 44 ]. Zhang et al found that B7-33 which targets relaxin family peptide receptors can activate hepatic stellate cells (HSCs) can weaken the fibrogenic properties of activated HSCs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…43 Once again, SK channels are interestingly correlated to this topic, as a few studies showed that both subtypes can be expressed in the liver and that the modulation of the SK2 subtype is beneficial against fibrotic liver injuries. 44,45 In another system entirely, SK2 channels are also investigated as potential targets for the treatment of Alzheimer's Disease and other pathologies reducing cognitive functions. In the central nervous system, SK channels are very well represented, with a predominance of the SK3 subtype in basal nuclei, while the main subtype in the cortical and hippocampal regions is SK2.…”
mentioning
confidence: 99%
“…Once again, SK channels are interestingly correlated to this topic, as a few studies showed that both subtypes can be expressed in the liver and that the modulation of the SK2 subtype is beneficial against fibrotic liver injuries. , …”
mentioning
confidence: 99%